Undetectable Changes in Image Resolution of Luminance-Contrast Gradients Affect Depth Perception - Tsushima, Yoshiaki; Komine, Kazuteru; Sawahata, Yasuhito; Morita, Toshiya (Frontiers in Psychology, 2016)
A great number of studies have suggested a variety of ways to get depth information from two dimensional images such as binocular disparity, shape-from-shading, size gradient/ foreshortening, aerial perspective, and so on. Are there any other new factors affecting depth perception? A recent psychophysical study has investigated the correlation between image resolution and depth sensation of Cylinder images (A rectangle contains gradual luminance-contrast changes.). It was reported that higher resolution images facilitate depth perception. However, it is still not clear whether or not the finding generalizes to other kinds of visual stimuli, because there are more appropriate visual stimuli for exploration of depth perception of luminance-contrast changes, such as Gabor patch. Here, we further examined the relationship between image resolution and depth perception by conducting a series of psychophysical experiments with not only Cylinders but also Gabor patches having smoother luminance-contrast gradients. As a result, higher resolution images produced stronger depth sensation with both images. This finding suggests that image resolution affects depth perception of simple luminance-contrast differences (Gabor patch) as well as shape-from-shading (Cylinder). In addition, this phenomenon was found even when the resolution difference was undetectable. This indicates the existence of consciously available and unavailable information in our visual system. These findings further support the view that image resolution is a cue for depth perception that was previously ignored. It partially explains the unparalleled viewing experience of novel high resolution displays.